High-entropy amorphous alloy flexible transparent electrode and preparation method and application thereof
By depositing a high-entropy amorphous alloy FeTaBTiW layer on a flexible transparent substrate, a high-entropy amorphous alloy flexible transparent electrode was prepared, which solved the shortcomings of the existing metal-based transparent electrodes in terms of thermal stability and transparency, and achieved high conductivity and good thermal stability.
Patent Information
- Application Number
- CN202411786640.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-01
AI Technical Summary
The existing metal-based transparent electrodes have shortcomings in thermal stability and transparency, and are prone to oxidation and corrosion, affecting conductivity and transparency.
A high-entropy amorphous alloy FeTaBTiW layer was used to deposit on a flexible transparent substrate, and a high-entropy amorphous alloy flexible transparent electrode (HEMG/PET) was prepared by magnetron cosputtering technology. This electrode had good transmittance and thermal stability.
It has achieved the improvement of thermal stability and transparency of high-entropy amorphous alloy flexible transparent electrodes, and has good conductivity and bending corrosion resistance, which is suitable for the field of flexible electronic devices.
Smart Images

Figure CN119736589A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flexible electrode preparation, and in particular to a high-entropy amorphous alloy flexible transparent electrode and a preparation method and application thereof. Background Art
[0002] Metal transparent electrodes are electrode materials that have attracted much attention in the fields of modern materials science and electronic technology. They cleverly combine the unique properties of metal materials with transparency.
[0003] Metal-based transparent electrodes have many outstanding features, and their high conductivity is a significant advantage. Taking silver nanowires as a typical example, silver itself is an excellent conductor, and metal-based transparent electrodes with silver nanowire network structures can achieve extremely low resistance. In organic light-emitting diode (OLED) display technology, traditional indium tin oxide (ITO) electrodes have some limitations, such as low mechanical strength, easy to produce microcracks under deformation conditions such as bending and stretching, resulting in a sudden drop in conductivity and other problems. The application of metal-based transparent electrodes, such as silver nanowire transparent electrodes, can effectively reduce the resistance of the electrode, thereby reducing the energy loss during charge transfer, so that the OLED screen can achieve a more uniform brightness distribution during display, improve the quality of image display, and be more cost-effective in large-size screen manufacturing. In wearable devices, metal-based transparent electrodes can adapt to various bends and deformations of the device in daily use without being easily damaged.
[0004] At present, there are some problems with the thermal stability of metal-based transparent electrodes, and their transparency is relatively limited, which faces challenges in some special application scenarios with extremely high transparency requirements. For example, the transparent electrode designed in patent CN118434170A often contains multi-layer electrodes to meet the optical path requirements, and the preparation process is complicated. Moreover, the chemical properties of metals are active and easily oxidized or corroded. Taking copper-based transparent electrodes as an example, in patent CN117255573A, copper easily reacts with oxygen in the air to form copper oxide on the surface, which greatly affects the conductivity and transparency of the electrode. In order to maintain its performance, special protective measures need to be taken, such as preparing a protective film on its surface or using it in a specific inert environment. In addition, many metals are easily oxidized with oxygen at high temperatures to form an oxide layer on the metal surface. Taking silver as an example, when heated to a certain temperature in the air, silver oxide will gradually form on the silver surface. The formation of an oxide layer will increase the resistance of the electrode, reduce its conductivity, and thus affect the performance of the transparent electrode. For some application scenarios with high transparency requirements, the oxide layer may also affect the transmittance of light and make the transparency of the electrode worse.
[0005] Optical transmittance and electrical conductivity are two key indicators for measuring metal-based transparent electrodes. Different combinations of metal-based transparent electrode materials and preparation processes can lead to huge differences in these two performance indicators. For example, by adjusting the type of metal, such as using different metals such as gold, silver, copper or their alloys; changing the thickness of the metal, a thinner metal layer may have a relatively high transparency but the conductivity may be reduced, while a thicker metal layer is the opposite; optimizing the composite structure, such as combining metal with other transparent materials, can optimize the balance of optical transmittance and electrical conductivity within a certain range. In touch screen technology, it is necessary to ensure that the screen has good visibility while ensuring the sensitivity of touch operation. By finely regulating the performance of metal-based transparent electrodes, the application requirements of touch screen technology on different devices can be met, such as smartphones, tablets, etc. Summary of the invention
[0006] The purpose of the present invention is to provide a high-entropy amorphous alloy flexible transparent electrode and a preparation method and application thereof. The flexible transparent electrode has good transmittance and thermal stability and a simple preparation process.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] The invention provides a high-entropy amorphous alloy flexible transparent electrode. The high-entropy amorphous alloy flexible transparent electrode comprises a flexible transparent substrate and a high-entropy amorphous alloy layer thereon.
[0009] Preferably, the flexible transparent substrate comprises polyethylene terephthalate (PET).
[0010] Preferably, the high entropy amorphous alloy (HEMG) layer is FeTaBTiW high entropy alloy.
[0011] Preferably, the atomic percentage range of each element in the FeTaBTiW high entropy alloy is: Ta 3-10%, Ti 10-35%, Fe 15-35%, W 30-50%, and B 3-15%.
[0012] Preferably, the high entropy amorphous alloy layer has a thickness of 10 to 70 nm.
[0013] More preferably, the thickness of the high entropy amorphous alloy layer is 12.5-62.5 nm, and even more preferably is 12.5 nm.
[0014] Preferably, the visible light transmittance of the high entropy amorphous alloy flexible transparent electrode is 35-86%, and the natural sheet resistance of the high entropy amorphous alloy flexible transparent electrode is not higher than 120Ω / sq.
[0015] In a second aspect, the present invention further provides a method for preparing the above-mentioned high entropy amorphous alloy flexible transparent electrode, the preparation method comprising the following steps:
[0016] A FeTaB target, a Ti target and a W target are co-sputtered, and a high entropy amorphous alloy layer is deposited on a pretreated flexible transparent substrate by a magnetron co-sputtering method to prepare the high entropy amorphous alloy flexible transparent electrode.
[0017] Preferably, the method for pre-treating the flexible transparent substrate is: using acetone, ethanol and deionized water to clean the PET substrate in sequence, and then drying it for standby use.
[0018] Preferably, the flexible transparent substrate rotates during the magnetron sputtering process, and the rotation speed is 5 to 8 r / min.
[0019] Preferably, the purity of the target material used for magnetron sputtering is greater than 99.99%.
[0020] Preferably, the background vacuum of the magnetron sputtering is less than 2×10 -3 Pa.
[0021] Preferably, the magnetron sputtering is performed in an Ar atmosphere, and the gas flow rate of the Ar atmosphere is in the range of 40 to 60 sccm.
[0022] Preferably, the sputtering working gas pressure is 0.5-1.5 Pa, the sputtering power is 60-130 W, and the sputtering time is 1-5 min.
[0023] Preferably, the distance between the target and the substrate is 4 to 8 cm.
[0024] Preferably, the preparation method further comprises a pre-screening process:
[0025] S1: placing three pre-treated flexible transparent substrates close to the FeTaB target, the Ti target, and the W target respectively, and fixing the three flexible transparent substrates so as not to rotate;
[0026] S2: Using FeTaB target, Ti target and W target for co-sputtering, three high entropy amorphous alloy flexible transparent electrodes with different atomic percentages of each element are obtained;
[0027] S3: Determine the light transmittance, and screen the transmittance of three high entropy amorphous alloy flexible transparent electrodes according to the light transmittance, and obtain the high entropy amorphous alloy flexible transparent electrode with the best transmittance, thereby determining the optimal atomic percentage of each element in the high entropy amorphous alloy layer in the high entropy amorphous alloy flexible transparent electrode.
[0028] In a third aspect, the present invention also provides an application of the above-mentioned high entropy amorphous alloy flexible transparent electrode in the field of flexible electronic devices.
[0029] The present invention utilizes magnetron sputtering technology, which is a widely used and relatively mature technical means in the field of thin film preparation, to prepare a high entropy amorphous alloy flexible transparent electrode (HEMG / PET) on a PET flexible substrate. The electrode is highly flexible, transparent and conductive, and has excellent flexibility and can maintain good electrical and optical properties under various deformation conditions such as bending and folding. In terms of stability, its performance is stable, and it can maintain stable performance and good repeatability after repeated use or under different environmental conditions. When faced with bending and corrosion in actual applications, the electrode exhibits good anti-bending and corrosion resistance. From the perspective of preparation technology, the process adopted by the present invention is relatively simple and the process is easy to control, which can not only ensure the stability of product quality, but also effectively reduce production costs, and has strong practical value and market competitiveness.
[0030] In the present invention, magnetron sputtering technology is used to prepare HEMG / PET flexible transparent electrodes, and the prepared HEMG / PET flexible transparent electrodes show an initial sheet resistance of 118.34Ω / sq. From an in-depth analysis from the perspective of electrical performance, the sheet resistance value shows that the electrode has a very outstanding performance in terms of conductivity. In the research field of flexible electrodes, low sheet resistance is often closely related to good conductivity. For flexible transparent electrodes, it is crucial to achieve efficient conductive properties while ensuring transparency. The HEMG / PET electrode obtained by the present invention can achieve such a sheet resistance value while having a certain flexibility and transparency, which is sufficient to prove that it has the extremely significant advantage of high flexibility, transparent conductivity, which lays a solid foundation for its use in many application scenarios that require flexibility, transparency and conductivity.
[0031] In the process of exploring the properties of HEMG / PET films, the present invention adopts a unique preparation method, that is, by fixing the PET substrate without rotating, a film group with different compositions is successfully obtained. This film group provides a rich sample for in-depth study of the relationship between film composition and performance.
[0032] High entropy amorphous alloys have good chemical stability. The FeTaBTiW system contains the corrosion-resistant element Ti, which makes the amorphous alloy show excellent resistance in the face of complex chemical environments. The characteristics of the amorphous phase further ensure that the electrode material has good corrosion resistance and can effectively prevent its performance from being corroded by chemical substances and degraded. The addition of the refractory element W not only increases the melting point of the high entropy material, but also gives it excellent thermal stability. In a high temperature environment, this material can maintain the integrity of its structure and performance and will not fail due to thermal decomposition, oxidation and other reactions. This is crucial for some equipment that works under high temperature conditions. For example, in the aerospace field, some components need to operate for a long time in a high temperature environment. FeTaBTiW high entropy amorphous alloy can be used as an electrode material to ensure the stable performance of the equipment under extreme temperature conditions.
[0033] In the study of the optical transmittance of the film, it was found that the element content in the film has a significant effect on the transmittance. Specifically, as the W content gradually increases, the transmittance of the film shows a trend that is not conducive to its improvement. This trend indicates that the W element may interfere with the propagation of light in the film to a certain extent, or interact with other components in the film, thereby reducing the overall transmittance. On the contrary, when the Ti content increases, the transmittance of the film will increase accordingly, indicating that the Ti element may help optimize the internal structure of the film, reduce light scattering or absorption, and thus improve the transmission efficiency of light in the film. This discovery provides a key theoretical basis for further precise regulation of the optical properties of HEMG / PET electrodes.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) The present invention prepares a HEMG / PET electrode by depositing FeTaBTiW high entropy alloy on a PET flexible substrate using magnetron sputtering technology. The HEMG / PET electrode has high transmittance and thermal stability, and the preparation process is relatively simple.
[0036] (2) The HEMG / PET electrode prepared by the present invention has a visible light transmittance of 35-86%, has high transparent conductive properties, and has excellent mechanical flexibility. This excellent flexibility makes the application of HEMG / PET electrodes in flexible devices have great potential.
[0037] (3) The HEMG / PET flexible transparent electrode prepared by the present invention exhibits an initial sheet resistance of 118.34Ω / sq and has high conductivity.
[0038] (4) The addition of refractory elements W, Ta, and Ti to the HEMG / PET flexible transparent electrode of the present invention not only increases the melting point of the high entropy material, but also gives it excellent thermal stability, and can maintain the integrity of its structure and performance in a high temperature environment.
[0039] (5) The HEMG / PET flexible transparent electrode prepared by the present invention has good repeatability and excellent stability.
[0040] (6) The HEMG / PET flexible transparent electrode prepared by the present invention does not require a multilayer structure and has good performance. The process adopted is relatively simple and the process is easy to control, which can not only ensure the stability of product quality, but also effectively reduce production costs, and has strong practical value and market competitiveness. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Schematic diagram of preparing HEMG / PET flexible transparent electrode according to the present invention;
[0042] Figure 2 Schematic diagram of a transmission spectrum analyzer (A) and a four-probe tester (B) used in the present invention to measure the transmittance and square resistance of HEMG / PET flexible transparent electrodes;
[0043] Figure 3 Actual pictures of the HEMG / PET flexible transparent electrodes prepared in Examples 1 (A) and 2 (B);
[0044] Figure 4 The transmission spectra of the HEMG / PET flexible transparent electrodes prepared in Example 1 and Example 2;
[0045] Figure 5 This is an X-ray diffraction pattern of the high entropy amorphous alloy layer of the HEMG / PET flexible transparent electrode prepared in Example 1;
[0046] Figure 6 DSC and DTG curves of the HEMG alloy film prepared in Example 3. DETAILED DESCRIPTION
[0047] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0048] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0049] Example 1
[0050] This embodiment provides a method for screening a HEMG / PET flexible transparent electrode with the best transparency performance, which is prepared by magnetron sputtering technology, and the specific steps are as follows:
[0051] a. Pretreatment of PET substrate:
[0052] The PET substrate was cleaned in an ultrasonic cleaner using acetone, ethanol, and deionized water for 15 minutes each, and then three PET films of 1×1 cm in size were fixed to three positions of the substrate using high-temperature tape. The three films were close to the three targets, respectively. Figure 1 As shown;
[0053] b. Preparation before film deposition:
[0054] First, confirm that the argon gas path and flow rate used in the experiment are normal, then clean the sputtering chamber and sample delivery room of the magnetron sputtering equipment, and install the target material to be sputtered in the sputtering chamber of the magnetron sputtering equipment (the target materials for sputtering thin films are FeTaB target, Ti target, and W target with a purity of 99.99% respectively);
[0055] The PET substrate obtained in step a was placed in the sputtering chamber of the magnetron sputtering equipment, and the mechanical pump was turned on to evacuate the sputtering chamber. When the vacuum degree was lower than 20 Pa, the molecular pump was turned on. When the vacuum degree of the sputtering chamber reached 2×10 -3 Sputtering begins at Pa.
[0056] c. Thin film deposition and packaging:
[0057] When the vacuum degree in the sputtering chamber reaches 2×10 -3 After the sputtering was completed, pure argon gas was introduced, the total sputtering pressure was adjusted to 0.7 Pa, the sputtering power was DC 100 W, the target was pre-sputtered for 5 min to clean the target, and then the sputtering film deposition was performed for 5 min (the three film substrates were fixed and not rotated during the sputtering process). After the sputtering was completed, the sample was taken out after the chamber was naturally cooled to room temperature for 30 min. The HEMG / PET flexible transparent electrode film samples prepared according to the above preparation scheme are shown in FIG. Figure 3 As shown in (A), the thickness of the HEMG layer sputtered on the PET substrate is 62.5 nm.
[0058] XRD diffraction analysis of the HEMG layer on the HEMG / PET flexible transparent electrode film, such as Figure 5 As shown, a diffraction peak appears at about 38°, indicating that the sputtered film is an amorphous structure at this power, and the peak intensity is relatively strong, indicating that the film has a high degree of amorphization.
[0059] Example 2
[0060] This embodiment provides a method for screening a HEMG / PET flexible transparent electrode with the best transparency performance, which is prepared by magnetron sputtering technology, and the specific steps are as follows:
[0061] a. Pre-treatment of PET substrate:
[0062] The PET substrate was cleaned in an ultrasonic cleaner using acetone, ethanol and deionized water for 15 minutes each, and then three PET films with a size of 1×1 cm were fixed to three positions of the substrate using high-temperature tape, with the three films being close to the three targets respectively;
[0063] b. Preparation before film deposition:
[0064] First, confirm that the gas path and flow rate of the argon gas used in the experiment are normal, then clean the sputtering chamber and sample delivery chamber of the magnetron sputtering equipment, and install the target material to be sputtered in the sputtering chamber of the magnetron sputtering equipment (the target materials for sputtering thin films are FeTaB target, Ti target, and W target with a purity of 99.99% respectively);
[0065] The PET substrate obtained in step a is placed in the sputtering chamber of the magnetron sputtering equipment, and a mechanical pump is turned on to evacuate the sputtering chamber.
[0066] c. Thin film deposition and packaging:
[0067] When the vacuum degree in the sputtering chamber reaches 2×10 -3 After the sputtering, pure argon gas was introduced, the total sputtering pressure was adjusted to 0.7Pa, the sputtering power was DC 100W, the target was pre-sputtered for 5min to clean, and then the thin film was deposited by sputtering for 1min (the three thin film substrates were fixed and not rotated during the sputtering process). After the sputtering was completed, the chamber was cooled to room temperature naturally for 30min before the sample was taken out. The HEMG / PET flexible transparent electrode film sample prepared according to the above preparation scheme is shown in FIG. Figure 3 (B) shows that the thickness of the HEMG layer sputtered on the PET substrate is 12.5 nm.
[0068] pass Figure 3 It can be seen that as the sputtering time decreases, the thickness of the high entropy amorphous alloy film decreases and the transmittance of the film increases.
[0069] The HEMG / PET flexible transparent electrode film prepared in Example 1 and the HEMG / PET flexible transparent electrode film prepared in Example 2 were tested for flexibility, transparency, and conductivity. The testing instrument is as follows: Figure 2 The test results are as follows:
[0070] Optical transmittance test:
[0071] Place the film samples flatly on the sample stage of the transmission spectrometer, and adjust the position of the sample stage so that the light can be incident vertically on the film surface. Set the integration time to 100ms, start the transmission spectrometer and record the measured transmittance data. The test results are as follows: Figure 4 As shown, FeTaB-rich is the HEMG / PET flexible transparent electrode film prepared near the FeTaB target, Ti-rich is the HEMG / PET flexible transparent electrode film prepared near the Ti target, and W-rich is the HEMG / PET flexible transparent electrode film prepared near the W target.
[0072] It can be found from the transmission spectrum that the transmittance of the film increases as the thickness of the film decreases, and the element content in the film has a significant effect on the transmittance. Because lattice distortion and increased defects will increase the scattering and absorption of light, thereby reducing the transmittance. Therefore, the transmittance of high-entropy amorphous alloys without lattice structures is higher than that of traditional alloys.
[0073] As the W content gradually increases, the transmittance of the film shows a trend that is not conducive to its improvement. This shows that the W element may interfere with the propagation of light in the film to a certain extent, reducing the overall transmittance. On the contrary, when the Ti content increases, the transmittance of the film will increase accordingly, and the maximum transmittance in the visible light region can reach 86%. This is because the band gap width of the film material determines its absorption capacity for light of different wavelengths. Materials with a wider band gap are less likely to be excited to transition electrons in the visible light range, and absorb less visible light, so the transmittance is high; while materials with a narrower band gap are more likely to have electrons absorb the energy of visible light and transition, resulting in enhanced absorption of visible light and reduced transmittance. Because the band gap width of tungsten (W) is relatively narrow, doping with the W element will enhance the material's ability to absorb visible light, resulting in poor transmittance.
[0074] Flexible transparent conductivity test:
[0075] The Ti-enriched film sample in Example 2 was placed on the test platform to ensure good contact between the sample and the platform. Figure 1 The square resistance test was performed using the four-probe tester shown in Figure 1. The probes were adjusted to be perpendicular to the film surface and evenly distributed on the sample. The film square resistance was measured to be 120Ω / sq by the automatic measurement program.
[0076] It can be seen from the test results of Examples 1 and 2 that the conductivity and flexible conductivity of the HEMG / PET electrode in the present invention are better than those of the commercial ITO / PET electrode.
[0077] In summary, based on the screening experiments of Example 1 and Example 2, the optimal atomic percentage ranges of each element in the high entropy amorphous alloy layer of the HEMG / PET flexible transparent electrode with the best transparency are as follows: Ta 3-10%, Ti 10-35%, Fe 15-35%, W 30-50%, and B 3-15%.
[0078] Example 3
[0079] Based on the optimal atomic percentage range of each element in the high entropy amorphous alloy layer determined by the screening experiments in Examples 1 and 2, this embodiment provides a method for preparing a HEMG / PET flexible transparent electrode, which is achieved by magnetron sputtering technology. The specific steps are as follows:
[0080] a.PET substrate pretreatment:
[0081] The PET substrate was cleaned in an ultrasonic cleaning machine using acetone, ethanol and deionized water respectively, with each cleaning lasting 15 minutes.
[0082] b. Preparation before film deposition:
[0083] First, the gas path and flow value of the argon gas used in the experiment were confirmed to ensure that they were in a normal state. Then, the sputtering chamber and sample delivery chamber of the magnetron sputtering equipment were cleaned, and the targets to be sputtered (FeTaB target, Ti target, and W target with a purity of 99.9%) were installed in the sputtering chamber of the magnetron sputtering equipment. The PET substrate treated in step a was placed in the sputtering chamber of the magnetron sputtering equipment. A PET film with a size of 1×1 cm was fixed between the three targets using a high-temperature tape, and a mechanical pump was started to evacuate the sputtering chamber.
[0084] c. Thin film deposition and packaging:
[0085] When the vacuum in the sputtering chamber reaches 2×10-3Pa, pure argon gas is introduced, the total sputtering pressure is adjusted to 0.7Pa, the sputtering power is set to DC 100W, and pre-sputtering is performed for 5 minutes to clean the target material. Subsequently, the DC target power is adjusted to 50W, the RF power target is adjusted to 130W, and the substrate rotation program is started for 1 minute of sputtering film deposition. After the sputtering is completed, wait for 30 minutes, wait for the chamber to cool naturally to room temperature, and then take out the sample, so that a uniform transparent electrode film is obtained.
[0086] Differential scanning calorimetry (DSC) and differential thermogravimetric analysis (DTG) experiments were performed on Example 3. The DSC and DTG curves are shown in FIG. Figure 6 As shown, it reflects the glass transition and crystallization process of the HEMG alloy film. It can be seen that its glass transition temperature T g is 777℃, the crystallization temperature Tx It is 1073℃, which means that the material can maintain an amorphous structure when working below this temperature, indicating that the prepared HEMG alloy film has good thermal stability.
[0087] Therefore, the present invention has the advantages of simple process, low cost, large-scale production, flexible and transparent conductive properties of transparent conductive metal film materials, and good stability, and can be applied to smart health, wearable electronics, intelligent robots and other fields.
[0088] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A high entropy amorphous alloy flexible transparent electrode, characterized in that: The high entropy amorphous alloy flexible transparent electrode comprises a flexible transparent substrate and a high entropy amorphous alloy layer thereon.
2. The high entropy amorphous alloy flexible transparent electrode according to claim 1, characterized in that: The flexible transparent substrate includes polyethylene terephthalate.
3. The high entropy amorphous alloy flexible transparent electrode according to claim 1, characterized in that: The high entropy amorphous alloy layer is FeTaBTiW high entropy alloy.
4. The high entropy amorphous alloy flexible transparent electrode according to claim 3, characterized in that: The atomic percentage range of each element in the FeTaBTiW high entropy alloy is: Ta 3-10%, Ti 10-35%, Fe 15-35%, W 30-50%, and B 3-15%.
5. The high entropy amorphous alloy flexible transparent electrode according to claim 1, characterized in that: The thickness of the high entropy amorphous alloy layer is 10-70 nm.
6. The high entropy amorphous alloy flexible transparent electrode according to claim 1, characterized in that: The visible light transmittance of the high entropy amorphous alloy flexible transparent electrode is 35-86%, and the natural sheet resistance of the high entropy amorphous alloy flexible transparent electrode is not higher than 120Ω / sq.
7. A method for preparing a high entropy amorphous alloy flexible transparent electrode according to any one of claims 1 to 6, characterized in that: The following steps are involved: A FeTaB target, a Ti target and a W target are co-sputtered, and a high entropy amorphous alloy layer is deposited on a pretreated flexible transparent substrate by a magnetron co-sputtering method to prepare the high entropy amorphous alloy flexible transparent electrode.
8. The method for preparing a high entropy amorphous alloy flexible transparent electrode according to claim 7, characterized in that: The flexible transparent substrate rotates during the magnetron sputtering process, and the rotation speed is 5 to 10 r / min; The purity of the target material used in the magnetron sputtering is greater than 99.99%; The background vacuum of the magnetron sputtering is less than 2×10 -3 Pa; The magnetron sputtering is performed in an Ar atmosphere, and the gas flow rate of the Ar atmosphere is in the range of 40 to 60 sccm; The sputtering working pressure is 0.5-1.5 Pa, the sputtering power is 60-130 W, and the sputtering time is 1-15 min; The distance between the target and the substrate is 4 to 8 cm.
9. The method for preparing a high entropy amorphous alloy flexible transparent electrode according to claim 7, characterized in that: The preparation method also includes a pre-screening process: S1: placing three pre-treated flexible transparent substrates close to the FeTaB target, the Ti target, and the W target respectively, and fixing the three flexible transparent substrates so as not to rotate; S2: Using FeTaB target, Ti target and W target for co-sputtering, three high entropy amorphous alloy flexible transparent electrodes with different atomic percentages of each element in the high entropy amorphous alloy layer are obtained; S3: Determine the light transmittance, and screen the transmittance of three high entropy amorphous alloy flexible transparent electrodes according to the light transmittance, and obtain the high entropy amorphous alloy flexible transparent electrode with the best transmittance, thereby determining the optimal atomic percentage of each element in the high entropy amorphous alloy layer in the high entropy amorphous alloy flexible transparent electrode.
10. Use of the high entropy amorphous alloy flexible transparent electrode as claimed in any one of claims 1 to 6 in the field of flexible electronic devices.